Evolutionary game analysis of clean heating governance in rural areas of Northern China - Liu, Wenlong; Li, Yunfeng; Zhu, Weiping (Frontiers in Environmental Science, 2022)
Promoting the realization of clean heating in rural areas of northern China is of great significance for environmental governance and the realization of the dual carbon goal. Based on the evolutionary game theory, this paper constructs a three-party evolutionary game model of central government, local government and farmers, and introduces important parameters such as local government's governance strength, central government's inspection strength, and two levels of government's subsidy strength into the model, and systematically deduces different possible strategy combinations of the three parties, and analyzes the possible scenarios and the stability conditions of each scenario. Finally, the paper simulates each scenario numerically and analyzes the influence of important parameters on the strategies of the three parties. The results show that (1) the strategy of local government has a decisive influence on farmers, and the central government's inspector strength has a weak effect on farmers. (2) The cost of clean heating over coal-fired heating has a significant effect on farm households, but not on the two levels of government. (3) The subsidy strength of both levels of government significantly pushes farmers to adopt clean heating, and when farmers' perceived indoor environmental benefits are low, they can be pushed to adopt clean heating by increasing the penalty strength. This study provides effective practical guidance and policy reference for the government to promote clean heating in rural areas.